Managing plant architecture for quality apples - Ahmed, N; Srivastava, K K; Kumar, Dinesh; Lal, Shiv (Indian Horticulture, 2024)
The plant architectural engineering offers good scope for quality apple production with high productivity per unit area through intensive orcharding. It is helpful in efficient utilization of natural resourceunder changing climatic scenario. The quality of apple fruits can be increased drastically with 80-90% fruits belonging to ‘A’ grade.